Filter Resin Kation Pelunak Air Sadah Sumur Gali - Winarni Kristanti; Narto Narto; Muryoto Muryoto (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Water quality which is not met the standard can cause disturbance and health problems. Waterthat contain high hardness can lead to soap wastefulness, forming precipitation and cookwarecrust, and become one of the risk factors for kidney failure. Various ways can be applied to reduce water hardness, one of which is filtration using ion exchange media. The ion exchangemedia used in this study is cation resin. The purpose of this study was to determine the effect ofcation resin thickness variation at filter on the decrease of well water hardness. This researchwas an experiment with pre-test post-test with control group design, and was conducted in January 2018, located in Pereng hamlet of, Bumirejo, Lendah, Kulon Progo Regency. The datawere analysed using one way anova. The average water hardness before processing was 460mg/l, while the mean decrease in the control group was 42,66 mg/l; in P1 group was 197,33 mg/l, in P2 group was 197,33 mg/l, and in P3 group was 197,33 mg/l. The results of data analysisshowed that the thickness variations of cation resin influence the decrease of well water hardness in the control group, and P1, P2, and P3 groups (p-value <0,001). The most effective cation resin thickness is the P3 group, i.e. filter with 11 cm thickness cation resin.